Macroeconomic policy transmission and international interdependence: A SVAR application to Brazil and US - Maria Helena Ambrosio Dias; Joilson Dias (EconomiA, 2013)
Economic policy transmission between trade partners has been analyzed over different contexts in the literature. Depending on real or nominal frictions, the results indicate possible beggar-thy-neighbor effects for policies, given international trade, and need for coordinating policies. The baseline model is Corsetti and Pesenti (2001) of macroeconomic interdependence. The theoretical proposition suggests that a no anticipated economic policy of exchange rate depreciation creates a beggar-thyself effect. Yet, many economies have engaged in this policy to enhance exports and improve welfare. Here, fiscal policy transmissions over Brazilian economic aggregates are investigated, considering Brazil as home and US as foreign country. The problem is specified in a Structural VAR (Vector Autoregression) model, taking Granger causality tests and Impulse Response analysis as econometric applications. The results indicate that expansionary fiscal policy in US has a beggar-thy-neighbor effect for the Brazilian economy in the long-run. The policy transmission mechanism relies on the terms of trade. In addition, real money balances are affected by foreign fiscal policy, affecting the efficiency of domestic monetary policy. – – Os efeitos de longo prazo da política fiscal sobre os agregados da economia brasileira s\~ao analisados dentro do contexto das inter-relaç\~oes macroeconômicas de países parceiros comerciais, Brasil e EUA. A investigaç\~ao empírica utiliza a análise Impulso Resposta, Causalidade de Granger com modelos de Vetores Auto-regressivos Estruturais (SVAR). Assim, desenvolvemos uma aplicaç\~ao do modelo de Corsetti & Pesenti (2001) de interdependência macroeconômica. Os resultados indicam que a política fiscal expansionista permanente nos EUA causa efeitos de empobrecimento da vizinhança no Brasil no longo prazo. O canal de transmiss\~ao da política é confirmado como os termos de troca. Além disso, os encaixes reais s\~ao também afetados de forma negativa pela política estrangeira, interferindo na eficiência da política monetária nacional.
Keywords: F41; F42; 330; Policy transmission; Fiscal policy; Beggar-thy-neighbor; SVAR